Implementation Plan in Response to The Board-Endorsed Recommendations From The IEO Evaluation Report on IMF Advice on Unconventional Monetary Policies. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2020)
The Management Implementation Plan was prepared before COVID-19 became a global pandemic and resulted in unprecedented strains in global trade, commodity, and financial markets. The actions in this plan and their timeline, therefore, do not reflect the implications of these developments and related policy priorities. The actions aim to: Strengthen in-house expertise on monetary policy; Deepen the work on UMP and related policies; Further strengthen financial spillover analysis; Explore ways to enhance the Fund's traction.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: United Kingdom